2005
DOI: 10.1007/s10151-005-0208-3
|View full text |Cite
|
Sign up to set email alerts
|

Long–term assessment of fecal incontinence after lateral internal sphincterotomy

Abstract: Incontinence due to LIS does not recover after long-term follow-up and appears to be an independent cause of fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 29 publications
0
23
0
4
Order By: Relevance
“…A major complication of internal sphincterotomy is fecal incontinence in anywhere from 5 to 31 percent of patients. [7][8][9][10][11][12] The fecal incontinence does not always recover, even after long-term follow-up. In one study of 68 patients undergoing internal sphincterotomy, fissures healed in 97 percent of patients, whereas 10.3 percent were incontinent and did not improve with time.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A major complication of internal sphincterotomy is fecal incontinence in anywhere from 5 to 31 percent of patients. [7][8][9][10][11][12] The fecal incontinence does not always recover, even after long-term follow-up. In one study of 68 patients undergoing internal sphincterotomy, fissures healed in 97 percent of patients, whereas 10.3 percent were incontinent and did not improve with time.…”
Section: Discussionmentioning
confidence: 91%
“…In one study of 68 patients undergoing internal sphincterotomy, fissures healed in 97 percent of patients, whereas 10.3 percent were incontinent and did not improve with time. 8 Nonetheless, lateral internal sphincterotomy is currently the standard of care for surgical treatment of fissures and is regarded as a safe and effective treatment, which only occasionally impairs continence. 1 Before the widespread acceptance of left-lateral internal sphincterotomy, several Bhistoric^proce-dures focused on obliterating all three components of the fissure: the fissure itself, the sentinel tag, and the hypertrophied papilla.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One group have shown that rates of continence impairment decreased from 45% within a week of surgery to 11.5% a month after the procedure [74]. However, in a second study with a low overall early incidence of incontinence (10.3%), these rates did not change with time [76]. A more recent study reported that rates of incontinence following LIS are similar to those in patients undergoing topical therapy [77].…”
Section: Sphincterotomymentioning
confidence: 88%
“…Disadvantages of internal sphincterotomy include; disturbance of continence, bleeding, fistula, abscess, persistent wound pain, cost and time of recovery [3]. These have led to search for another mode of therapy or pharmacologic way to create a temporary or reversible sphincterotomy, one that would lower the sphincter pressure only until the fissure healed [4].…”
Section: Introductionmentioning
confidence: 97%